األدب في عصر الذكاء االصطناعي د ارسة تحليلة في آفاق وتحوالت التذوق الجمالي. - صديقة بشرى علي مح خالد علي ادريس م&#1581 (Arab Journal for Humanities & Social Sciences, 2026)
This study, "Literature in the Age of Artificial Intelligence: An Analytical Study of the Horizons and Transformations of Aesthetic Taste," was conducted to shed light on the gray area between human emotion and digital algorithms. The researcher employed a combination of methodologies to suit the study's subject matter, including structured observation, systems analysis, and descriptive-analytical methods. While some view these technologies as a threat to the privacy of human creativity, others see them as a new horizon that expands the scope of artistic expression. This research seeks to analyse how artificial intelligence has reshaped "literary taste" and how the contemporary reader has responded to texts where human expression intertwines with programming code, attempting to envision the future of "beauty" in the age of intelligent machines. After conducting interviews with the remaining study sample, the researcher arrived at several key findings, including: 1. Critics tend to view artificial intelligence as a skilled "simulator" rather than an original "creator," due to its lack of conscious intentionality. 2. There is significant concern (high average score) regarding issues of digital plagiarism and the loss of intellectual property rights. 3. The concept of "hybrid literature" is accepted as a tool to aid in editing or idea generation (brainstorming), not in writing the final text. The study also reached several key recommendations, including: 1. The need to develop a new critical framework that establishes clear criteria for evaluating machine-generated texts. 2. Encouraging critics to focus on the "aesthetics of reception" of digital texts, rather than solely on the "author's identity".